COMPLEX THERAPY OF CHILDREN WITH MUCOVISCIDOSIS. RECOMMENDATIONS OF A PEDIATRICIAN - O.I. Simonova (Union of pediatricians of Russia, 2006)
Treatment of children's mucoviscidosis is a multicomponent complex of medical and non medicamental types of therapy. The earlier the basic mucoviscidosis treatment has started, the more favourable the diagnosis for the patient will be. The article gives particular recommendations for the pediatrician on the mucoviscidosis therapy along with the copies of orders that specify these patients to be provided with the medications, and clinical pattern with the detailed indication of the applied medications.Key words: mucoviscidosis among children, complex therapy.